Analysis of the Effect of Sharia Microfinance on Economic Growth of UMJ Food Court MSMEs - Irgy Sasy Ramandha; Adi Mansah (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the effect of Islamic microfinance on the economicgrowth of Micro, Small, and Medium Enterprises (MSMEs) in the food court at the Universityof Muhammadiyah Jakarta (UMJ). The research method used is a qualitative approach withdata collection techniques through in-depth interviews, observations, and document analysis.The results of the study indicate that Islamic microfinance provides a significant contributionto the economic growth of MSMEs by increasing capital accessibility, strengthening financialmanagement, and encouraging business innovation. This study concludes that Islamicmicrofinance is an effective instrument to support the development of MSMEs in highereducation environments